MeasurMeasuring The Size of The Black Economy in Iraq and Analyzing Its Economic and Social Impactsing the size of the black economy in Iraq and analyzing its economic and social impacts: A study analytical - Abdulwahid, Oday Ibrahim; Ibrahim, Mustafa Ali; Saeed, Yasir Jihad (Indonesian Journal of Law and Economics Review, 2026)
Background: The black economy undermines fiscal sustainability and policy effectiveness in developing nations. Specific Context: Iraq faces structural challenges including weak governance, political instability, and high unemployment, exacerbating informal economic activities. Gap: Existing Iraqi studies lack rigorous quantitative measurements using advanced models. Aim: This study measures Iraq's black economy (2004-2023) using the MIMIC model. Results: Corruption, tax burden, unemployment, and political crises significantly expand the informal economy, while improved governance reduces it. Novelty: First comprehensive application of MIMIC model with integrated causal-indicator framework for Iraq. Implications: Findings inform evidence-based policies for institutional reform, tax system simplification, and financial inclusion to mitigate informal economic activities.Highlight : MIMIC model identifies corruption, tax burden, unemployment, and political crises as primary drivers of Iraq's black economy (2004-2023). Black economy peaked during instability periods (2006-2007, 2014-2016, 2020); improved governance reduces informal activities. Governance reform, tax system simplification, and financial inclusion are key to integrating informal activities into formal economy. Keywords : Shadow Economy, MIMIC Model, Iraq, Governance, Tax Burden, Corruption